Analisis Hasil Uji Kompetensi Guru Fisika - Fauzi Bakri; Sabar Budi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
AbstractThis study aims to map the pedagogical competence and professional competence of teachers high school physics teacher competency test participants (UKG) in 2012. The study was conducted qualitatively by exposure method facto supported the survey results in the form of FGD field visits in 2013 to 2015. The research data is secondary data test results of high school physics teacher competence and FGD data obtained from a visit to several cities in several provinces. Teacher competency test secondary data obtained from the Center for Professional Development of Teachers (PUSBANGPRODIK) Kemdikbud. Teacher competency test was mapped by the standard of essential indicators of teacher competence. For pedagogical competence there are 22 essential indicators, while professional competence are 59 essential indicators. Teacher competency test results in 2012 illustrate that there is one indicator pegagogik at the lowest level, 12 indicators at low levels, while the professional indicator has one indicator at a very low level, 25 indicators at low levels. Based on the results of focus group discussions and field surveys conducted in several high schools in several provinces in 2013 and 2015 found that teachers are less creative in designing scientific learning student-centered. Teachers lack pedagogical training and training to improve the mastery of concepts of physics. Availability of laboratory experiments are also very limited. Textbooks to support the professional competence of teachers of physics that is not owned by the school library.Keywords: competence, pedagogical, professional, UKG, the essential indicatorAbstrakPenelitian ini bertujuan untuk memetakan kompetensi pedagogik dan kompetensi profesional guru fisika SMA peserta uji kompetensi guru (UKG) tahun 2012. Penelitian dilakukan secara kualitatif dengan metode ekspos fakto yang didukung hasil survei berbentuk FGD dalam kunjungan lapangan tahun 2013 sampai 2015. Data penelitian adalah data sekunder hasil uji kompetensi guru fisika SMA dan data FGD yang didapat dari kunjungan ke beberapa kota di beberapa provinsi. Data sekunder uji kompetensi guru didapat dari Pusat Pengembangan Profesi Pendidik (PUSBANGPRODIK) Kemdikbud. Soal uji kompetensi guru dipetakan berdasarkan indikator esensial standar kompetensi guru. Untuk kompetensi pedagogik terdapat 22 indikator esensial, sedangkan kompetensi profesional terdapat 59 indikator esensial. Hasil uji kompetensi guru pada tahun 2012 memberikan gambaran bahwa ada satu indikator pegagogik pada level paling rendah, 12 indikator pada level rendah, sedangkan indikator profesional memiliki satu indikator pada level sangat rendah, 25 indikator pada level rendah.Berdasarkan hasil FGD dan survey lapangan yang dilakukan di beberapa SMA di beberapa provinsi pada tahun 2013 sampai 2015 didapat bahwa guru kurang kreatif dalam merancang pembelajaran saintifik yang berpusat pada siswa. Guru kurang mendapat pelatihan pedagogik maupun pelatihan peningkatan penguasaan konsep fisika. Ketersediaan alat praktikum di laboratorium juga sangat terbatas. Buku teks untuk menunjang kompetensi profesional guru fisika yang tidak dimiliki oleh perpustakaan sekolah.Kata-kata kunci: Kompetensi, pedagogik, profesional, UKG, indikator esensial